DAMPAK SINO-MYANMAR PIPELINE TERHADAP PEMBANGUNAN EKONOMI MYANMAR: ANALISIS TERHADAP HUMAN DEVELOPMENT INDEX (HDI) 2014-2022 - Olivia Putri Harludi; Sonny Sudiar (Laboratorium Dinamika Sosial Global Hubungan Internasional FISIP UNMUL, 2025)
The Sino-Myanmar Pipeline is a key infrastructure project within the China-Myanmar Economic Corridor (CMEC) and is expected to contribute to human development in Myanmar. This study examines the project’s contribution to the Human Development Index (HDI) and evaluates its impact based on Todaro and Smith’s three dimensions of human development: sustenance, self-esteem, and freedom. Using a mixed-method sequential explanatory approach, the research begins with quantitative analysis of macroeconomic indicators and HDI data, followed by qualitative analysis using reports, government documents, and relevant literature. The findings show that the project’s direct contribution to HDI is minimal, approximately 0.00011 points, indicating that its economic benefits have not significantly improved people’s well-being. In terms of sustenance, income gains remain limited; in self-esteem, employment opportunities and CSR programs have not yielded meaningful capacity building; and in freedom, social and political constraints persist. Overall, the project functions as a double-edged sword, offering development opportunities while simultaneously presenting risks that must be carefully managed.